2023
DOI: 10.55131/jphd/2023/210212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of binge drinking behavior among working-age populations in Thailand using GIS: A national survey in 2017

Abstract: This study identifies the prevalence of binge drinking behaviour and the statistical relationship between local patterns and binge drinking behaviour among the working-age population in Thailand. This study was conducted using The Smoking and Drinking Behaviour Survey 2017 data set from the National Statistical Office of Thailand. Local Indicators of Spatial Association (LISA) were used to identify the spatial autocorrelation between surrounding areas, with binge drinking behaviour among the working-age popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The increases in alcohol excise tax are inconsistent with the economic shifts that could be attributed to inflationary changes in the era of globalization, which also found that there was an intervention in the alcohol control policy according to the economic benefits of the country in each period (Chaiyasong et al, 2011;Prasit et al, 2023), As with most policies, there are intended outputs and unintended consequences. According to the study carried out in Australia, it is predicted that alcohol consumers with low income might be able to control the frequency and level of regular alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The increases in alcohol excise tax are inconsistent with the economic shifts that could be attributed to inflationary changes in the era of globalization, which also found that there was an intervention in the alcohol control policy according to the economic benefits of the country in each period (Chaiyasong et al, 2011;Prasit et al, 2023), As with most policies, there are intended outputs and unintended consequences. According to the study carried out in Australia, it is predicted that alcohol consumers with low income might be able to control the frequency and level of regular alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%